FINANCIAL RATIO ANALYSIS TO ASSESS FINANCIAL PERFORMANCE OF COOPERATIVES - Suwarto Suwarto (UNIVERSITAS MUHAMMADIYAH METRO, 2018)
Financial performance analysis of KSPPS BMT Ar-Rahmah Mitra Insani is done in relation to the significant decrease of business income (SHU) in the last few years. The purpose of the research is to determine the financial performance of KSPPS BMT Ar-Rahmah period 2014-2016 based on the standard Regulation of the Minister of Cooperatives and SME RI No.06/Per/M.KUKM/V/2006 on Guidelines for Assessment of Cooperative Achievement in terms of calculation of Ratio Liquidity, Solvency and Profitability/Profitability Ratio. The method used is quantitative method with descriptive format. Analyzer used in this research include liquidity ratio by using current ratio calculation technique, solvency ratio by using technique of total debt to asset and total debt to own capital, profitability/rentability ratio with own capital rentability calculation technique, Return On Asset (ROA ) and Net Profit Margin (NPM). The results of the research shows that the financial performance of KSPPS BMT Ar-Rahmah Mitra Insani in terms of profitability, liquidity and solvency in general is still below the standard of Minister of Cooperatives and SME RI No.06 /Per/M.KUKM/V/2006 with bad criteria and less good. Keywords: Financial performance, Financial ratio